Customer Experience as A Mediator Between AI Personalization and Consumer Loyalty: Evidence From Shopee Users - Eko Wardoyo; Dani Rizana (Indonesian Journal of Business and Entrepreneurship Research, 2026)
The rapid development of artificial intelligence (AI) has transformed digital marketing practices, particularly through personalization strategies that enhance consumer interactions. This study aims to examine the effect of AI personalization on customer experience and consumer loyalty, as well as the mediating role of customer experience in the relationship between AI personalization and consumer loyalty on digital platforms. This research adopts a quantitative approach using survey data collected from users of digital platforms. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test the proposed relationships among the variables. The results indicate that AI personalization has a positive and significant effect on customer experience and consumer loyalty. Furthermore, customer experience significantly influences consumer loyalty and mediates the relationship between AI personalization and consumer loyalty. These findings highlight that AI-driven personalization can enhance experiential value, which in turn strengthens consumer loyalty. This study contributes to the digital marketing and customer experience literature by providing empirical evidence on how AI-based personalization mechanisms shape consumer loyalty in digital environments.